Immune-Based Therapy for Hospitalized Patients With COVID-19 and Risk of Secondary Infections: A Systematic Review and Meta-analysis. (7th December 2022) - Kabbani, Dima; Sonpar, Ashlesha; Weyant, Benson; Lau, Keith C K; Robbins, Mark; Campbell, Sandra; Doucette, Karen; Abraldes, Juan G; Lotfi, Tamara; Chaktoura, Marlene; Akl, Elie A; Cervera, Carlos
Abstract: Background: Immune-based therapies are standard-of-care treatment for coronavirus disease 2019 (COVID-19) patients requiring hospitalization. However, safety concerns related to the potential risk of secondary infections may limit their use. Methods: We searched OVID Medline, Ovid EMBASE, SCOPUS, Cochrane Library, clinicaltrials.gov, and PROSPERO in October 2020 and updated the search in November 2021. We included randomized controlled trials (RCTs). Pairs of reviewers screened abstracts and full studies and extracted data in an independent manner. We used RevMan to conduct a meta-analysis using random-effects models to calculate the pooled risk ratio (RR) and 95% CI for the incidence of infection. Statistical heterogeneity was determined using the I 2 statistic. We assessed risk of bias for all studies and rated the certainty of evidence using the Grading of Recommendations Assessment, Development, and Evaluation methodology. We conducted a meta-regression using the R package to meta-explore whether age, sex, and invasive mechanical ventilation modified risk of infection with immune-based therapies. The protocol is registered with PROSPERO (CRD42021229406). Results: This was a meta-analysis of 37 RCTs including 32 621 participants (mean age, 60 years; 64% male). The use of immune-based therapy for COVID-19 conferred mild protection for the occurrence of secondary infections (711/15 721, 4.5%, vs 616/16 900, 3.6%; RR, 0.82; 95% CI, 0.71–0.95; P = .008; I 2 = 28%). A subgroup analysis did not identify any subgroup effect by type of immune-based therapies ( P = .85). A meta-regression revealed no impact of age, sex, or mechanical ventilation on the effect of immune-based therapies on risk of infection. Conclusions: We identified moderate-certainty evidence that the use of immune-based therapies in COVID-19 requiring hospitalization does not increase the risk of secondary infections.